Tindak Pidana Korupsi dalam Konteks Pertanggungjawaban Pidana Korporasi - Parameshwara Parameshwara; Khairul Riza (Penerbit Goodwood, 2023)
Purpose: This research is aim to know the arrangements of the law of criminal acts corruption is responsible to the matter of criminal corporation and to know the law analysis of the responsibility of criminal corporations in criminal acts corruption. Methodology: This research uses the normative law (normative juridiction) approach by using the laws approach, conceptual approach, dan comparative and empirical approach (field data). Result: The results show that legal arrangements for corruption in the context of criminal corporations responsibility, which is regulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes state that corporations can be punished if they violate the provisions in the Law on the Eradication of Criminal Acts Corruption, and sanctions that can be given include fines and revocation of business licenses. Law analysis of the responsibility of criminal corporations in criminal acts corruption that is the responsibility of criminal corporate in criminal acts corruption can be applied by considering the negative and positive effects from criminalize a company that is involved in criminal acts of corruption. Theoretically, criminalizing a company that is involved can be considered a good act because it gives wary effects on the company and prevents other companies to do so., nevertheless it need to consider the advantages of corporate sustainability for the best benefit for stockholder or stakeholder.